2014
DOI: 10.13189/ujmr.2014.020101
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Diversity of a Water Body in the Niger Delta as Affected by Refinery Effluent

Abstract: The microbiological quality of refinery effluent, and water and sediments of the effluent receiving Okrika sector of bonny estuary was investigated. Treated waste water (TWW) recorded the highest total heterotrophic bacteria (THB) of 1.6 X 109 cfu/ml, while raw waste water had the highest bacterial diversity of 24.82%. The THB population of the water body was lowest [8.6X103cfu/ml] at the effluent outfall site (SS1) in January compared to the highest [1.10X108cfu/ml] recorded at the control station (SS6). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Ogbonna et al [35] reported higher total bacteria counts (1.12±0.13x10 8 to 1.28±0.09x10 8 cfu/m) in surface water. The bacteria and fungi isolated and identified in this study are similar to those reported by several researchers in similar ecosystems [26,36,37]. The preponderance of coliform group of bacteria in the estuary water in our study is a calls for concern as it indicates recent faecal contamination [29,38].…”
Section: Discussionsupporting
confidence: 88%
“…Ogbonna et al [35] reported higher total bacteria counts (1.12±0.13x10 8 to 1.28±0.09x10 8 cfu/m) in surface water. The bacteria and fungi isolated and identified in this study are similar to those reported by several researchers in similar ecosystems [26,36,37]. The preponderance of coliform group of bacteria in the estuary water in our study is a calls for concern as it indicates recent faecal contamination [29,38].…”
Section: Discussionsupporting
confidence: 88%